Pengaruh Corporate Governance, Struktur Modal, dan Firm Growth terhadap Financial Distress pada Perusahaan Sektor Consumer non-cyclicals yang terdaftar di BEI periode 2020-2023 - Elsa Vani Hikmah; Listiya Ike Purnomo (Jurnal Riset Pendidikan Ekonomi, 2026)
This This study aims to examine the effect of corporate governance, capital structure, and firm growth on financial distress in consumer non-cyclical companies listed on the Indonesia Stock Exchange during the period 2020–2023. This is a quantitative study with a descriptive and verificative approach. The sample was selected using purposive sampling from 78 companies, resulting in 72 companies, and after outlier testing, 55 companies remained. Data were collected through financial statement documentation. The research variables include financial distress as the dependent variable, and corporate governance (managerial ownership and number of board members), capital structure, and firm growth as independent variables. Data analysis was conducted using EViews 12, including descriptive statistics, panel data regression, classical assumption tests, and hypothesis testing. The results indicate that corporate governance, capital structure, and firm growth significantly influence financial distress simultaneously. Partially, capital structure has a negative effect, while corporate governance and firm growth do not have a significant effect. These findings emphasize the importance of capital structure management in reducing the risk of financial distress.